Contextos materiales de desigualdad social en el valle de Ambato, Catamarca, Argentina, entre los siglos VII y X d.C. - Laguens, Andrés G. (Revista Española de Antropología Americana, 2007)
In the Valle de Ambato, Catamarca, Argentina, at 7th century A.D. it is registered a new social configuration held around the maintenance of inequalities among people, sustained by structures and mechanisms of differentiation and heterogeneity acting at diverse material and nonmaterial spheres. This paper examines the spatial dimension of social practices and the differential access to material culture, ceramic technology and to environmental exploitation, in order to solve in terms of the archaeological record which were the main components taking part in a social differentiated system, as well as their relationships and change. It is proposed that the volume of managed resources was a key factor in stating differences between people, being the built environment and the space the most important resources in the material realms of social inequality.